Structural Inequality Linked to Brain Volume and Network Dynamics in Aging and Dementia Across the Americas - Garcia-Serrano, A (Springer, 2025)
Structural inequality, the uneven distribution of resources and opportunities, influences health outcomes. However, the biological embedding of structural inequality in aging and dementia, especially among underrepresented populations, is unclear. We examined the association between structural inequality (country-level and state-level Gini indices) and brain volume and connectivity in 2,135 healthy controls, and individuals with Alzheimer’s disease and frontotemporal lobe degeneration from Latin America and the United States. Greater structural inequality was linked to reduced brain volume and connectivity, with stronger effects in Latin America, especially in the temporo-cerebellar, fronto-thalamic and hippocampal regions. In the United States, milder effects were observed in the insular-cingular and temporal areas. Results were more pronounced in Alzheimer’s disease and were independent of age, sex, education, cognition and other confounding factors. The findings highlight the critical role of structural inequality in aging and dementia, emphasizing the biological embedding of macrosocial factors and the need for targeted interventions in underserved populations. © The Author(s), under exclusive licence to Springer Nature America, Inc. 2024.